Maria Sebagai Bintang Evangelisasi Baru - Dominikus Doni Ola; Mawarni Gea; Carniawati Laia (STP Dian Mandala Gunungsitoli Nias Keuskupan Sibolga, 2024)
Mary is the Mother of God and Mother of the Church. She was God's chosen woman who became the mother of Jesus. Mother Mary has a major role in the mystery of God's work of salvation. The main issue raised by the author is who Mary is in the life of Christians and why Mary is called the star of the new evangelization. The purpose of this writing is to talk about Mary as the new star of evangelization for Christians. The method used in this thesis is the literature review method. The discussion obtained is that Mary is the star of the new evangelization. Mary, Mother of the Redeemer, is also the Mother of the Church who is an example in proclaiming the joyful news of the Gospel. Mother Mary did not abandon the role that brought salvation, but she continued to obtain for Christians the gifts that lead to salvation. So that Christians understand how to proclaim the Gospel joyfully and be ready to respond to God's call. So, it is recommended for Christians, Catholic Religious Teachers to be actively involved in preaching the joyful news of the Gospel.